Environmental factors affecting entomopathogenic fungi in the soil - Mccoy, Clayton W.; Storey, Greggory K.; Milani, Myrian Silvana Tigano (Pesquisa Agropecuaria Brasileira, 1992)
In the last decade, chemical pesticide substitutes for the organochlorine compounds have been less persistent and effective as soil insect controls resulting in more soil pests with greater importance in agriculture. Concurrently, environmental quality has become a major issue in the use of certain chemical pesticides in the soil resulting in more cancellations and restrictions for use. Because of environmental concerns and the astronomical increase in pesticide developmental costs, agrochemical companies worldwide are, for the first time, making a serious commitment to the development of biopesticides for soil insect control. Fungi within the Zygomycotina, the Ascomycotina and the Deuteromycotina occur in many soil habitats where many insects spend their lives permanently or, most frequently, temporarily in the soil. From this association, 11 fungal genera have evolved as pathogens of soil-inhabiting insects. The genera Beauveria, Metarhizitan and Paecilomyces, commonly infect all stages of many insect species and have been scrutinized as potential biopesticides. However entomopathogenic fungi of the soil, just as subterranean insects, are affected by abiotic factors, mainly temperature, relative humidity or soil water content, agrochemicals and soil composition. Biotic factors such as other soil microorganisms, soil arthropods and even plants influence their survival. The interactions between the microflora and the fauna of the soil are numerous and are greatly influenced by physiochemical factors of the habitat.